[PP.LB02.17] FACTORS ASSOCIATED WITH HIGH AMBULATORY BLOOD PRESSURE AMONG TREATED HYPERTENSIVE PATIENTS. WINTER AND SUMMER COMPARISON. (September 2016) - Koshelyaevskaya, Y.; Smirnova, M.; Gorbunov, V.; Volkov, D.; Boytsov, S.; Loukianov, M.; Deev, A.; Dolotovskaya, P.; Dovgalevskij, P.; Furman, N.; Puchin'yan, N.
Abstract : Objective: Influence of antihypertensive therapy (AHT) on clinical (CBP) and ambulatory BP (ABP) associated with cardiovascular prognosis. But the factors associated with high ABP among treated hypertensive patients (THP) in different seasons are studied less. The aim of this study was to analyse factors associated with high ABP of THP in different seasons (winter [W] and summer [S]). Design and method: We extracted THP from the part of the 2012–2014 database (n = 1446). The main entry criteria were: residence in Saratov, regular AHT (>2 weeks) and availability of CBP and ABP monitoring (ABPM) measurements in W and in S. Normal CBP definition was CBP<140/90 mmHg. Normal ABP definitions were 24ABP<130/80 mmHg, and dayABP<135/85 mmHg, and nightABP<120/70 mmHg. Results: The total number of THP was 245: 56% men, mean age 58.3 ± 0.6 (M ± m) years, body mass index (BMI) 28.0 ± 0.3 kg/m 2, CBP at entry 127.4 ± 0.9/75.6 ± 0.6 mmHg. The number of patients with high CBP and high-normal ABP (uncontrolled hypertension [UH]/white coat hypertension) in W: 97/7; with normal CBP and high-normal ABP (masked uncontrolled hypertension [MUH]/effective AHT): 91/50. The number of patients with high CBP and high-normal ABP: 68/4; with normal CBP and high-normal ABP in S: 127/46. The factors associated with UH (p < 0.05): sex (W, S), age (W, S), height (W), body mass (BM; W). Factors associated with MUH (p < 0.05): BM (W, S), CBP parameters (included orthostatic BP; W, S); sex (W), height (W), smoking (W), BMI (S), heart rate (S). Conclusions: Traditional risk factors associated with high ABP, but do not depend on seasons. Factors associated with increased ABP in UH are body mass and height in W; MUH are sex, height and smoking in W; BMI, heart rate in S. These factors among patients with normal CBP are the reason for more intensive using of ABPM, especially among smokers and patients with a high body mass.